Impact of a diagnostic therapeutic educational pathway program for asthma management in preschool children - Sebastiano Guarnaccia; Cristina Quecchia; Andrea Festa; Michele Magoni; Giuseppe Zenoni; Emanuele D'Agata; Valentina Brivio; Elena Zanardini; Carmelo Scarcella; Valeria Gretter; Susanna Facchetti; Cinzia Gasparotti; et al. (BMC, 2021)
Abstract Background Preschool children with clinically-diagnosed asthma have a higher rate of emergency department visits and consume more resources for management than older children. However, no clinical trials have yet been performed measuring the impact of a combined diagnostic, therapeutic and educational pathway regimen for evaluation of wheezing control in children aged less than 6 years. The purpose of the present study was to assess the impact of a pediatric program developed in Italy, the Diagnostic Therapeutic Educational Pathway (DTEP), for asthma management in children less than 6 years old attending an asthma referral center. Methods This is a retrospective population-based cohort study performed in children with asthma aged 0-5 years, attending at "Io e l'Asma center", Brescia, Italy between September 2007 and December 2014. The incidence rates (IRs) of hospitalization, emergency room visits, use of outpatient services and drug usage for dyspnea, wheezing, or respiratory symptoms were evaluated for time periods prior to and after DTEP intervention. Results A total of 741 patients, aged 0-5 years completed the DTEP, including 391 and 350 children aged 0-2 and 3-5 years, respectively. The percentage of children aged 0-2 and 3-5 years showing improved control of wheezing symptoms during the 1st to 3rd visit interval as a result of the DTEP intervention increased from 39.5 to 60.9% and from 25.5 to 75.5%, respectively. During these periods, the IRs showed a significant decrease for all outcomes, from-8.6% to − 80.4%. Although specific IRs for drug prescriptions declined, particularly for LABA plus corticosteroids, antibiotics, and systemic corticosteroids, they increased for SABA, inhaled corticosteroid and leukotriene receptor antagonist usage. Conclusions The results suggest that a real-world assessment of the integrated DTEP program for preschool children provides evidence for improved wheezing control and reduction of adverse therapeutic related outcomes.